Change in Atrial Activation Pattern during Ablation of Atrial Flutter - Mohammad Ali Akbarzadeh; Abolfath Alizadeh Diz; Negar Bahrololoumi Bafruee (Publisher: Shahid Beheshti University of Medical Sciences, 2016)
Different types of supraventricular tachycardia have been reported in patients with history of surgical repair of Tetralogy of Fallot. This report presents appearance of focal atrial tachycardia during radiofrequency ablation of the cavotricuspid isthmus